The Political Economy of ECFA Impact Between China-Taiwan and the ASEAN States: Opportunity and Challenges. Issue 6 (1st November 2016) - Huang, Michael C.; Soong, Jenn-Jaw
Abstract : The Cross-strait Economic Cooperation Agreement (ECFA), signed on in 2010 between China and Taiwan, is the first regional preferential agreement for Taiwan, which is seen as a significant turning point in China-Taiwan relations and a landmark to promote Asia's overall economic development. This article introduces the ECFA's aim and discusses its implications for future economic relations between China and Taiwan while reviewing overall and specific statistics data of trades and investment flows. With the fourth anniversary of the enactment of the ECFA, the trade volume seems to increase, but the trends and components shows a further integration in the region, implying the post-ECFA trend sheds light on China and Taiwan's solid cooperation on production networks of information, communication, and solar panel related products with ASEAN countries, as well as the RMB internationalization opportunity for the future AIIB framework for China.